التنمر المدرسي وعلاقته بالتوافق الدراسي لدى تلاميذ مرحلة التعليم الثانوي -دراسة ميدانية بثانوية المجاهد شوية جباري ورماس - شيماء نذير; مسغونة سلسبيل (جامعة الوادي - University of Eloued, 2025)
" تهدف الدراسة الحالية إلى كشف عن العلاقة بين التنمر المدرسي والتوافق الدراسي لدى عينة من تلاميذ سنة أولى والثانية من تعليم الثانوي بجميع الشعب والبالغ عددهم 146 تلميذ وتلميذة وطبقت الدراسة بثانوية المجاهد شوية جباري بلدية ورماس ولاية الوادي وتم تطبيق مقياسين: مقياس التنمر المدرسي ومقياس التوافق الدراسي وذلك بعد التأكد من خصائص السيكومترية لأدوات الدراسة . وتوصلت الدراسة إلى: -توجد علاقة بين التنمر المدرسي والتوافق الدراسي مع التلاميذ –توجد علاقة بين التنمر المدرسي والتوافق الدراسي مع الأساتذة -لا توجد علاقة بين التنمر المدرسي والتوافق الدراسي مع المنهاج –توجد علاقة بين التنمر المدرسي والتكيف مع المدرسة وتوصلت الدراسة الى : توجد علاقة بين التنمر المدرسي والتوافق الدراسي لدى تلاميذ مرحلة التعليم الثانوي "The current study aims to reveal the relationship between school bullying and academic adjustment among a sample of first- and second-year high school students from all academic tracks, totaling 146 male and female students. The study was conducted at Chouia Jebbari High School, located in the municipality of Ourmas, El Oued Province. Two scales were used: a school bullying scale and an academic adjustment scale, after confirming the psychometric properties of the research instruments. The study found that: • There is a relationship between school bullying and students’ academic adjustment. • There is a relationship between school bullying and adjustment with teachers. • There is no relationship between school bullying and adjustment to the curriculum. • There is a relationship between school bullying and adjustment to the school environment. The study concluded that there is a relationship between school bullying and academic adjustment among high school students. "
مذكرة ماستر قسم علم النفس وعلوم التربية تخصص إرشاد وتوجيه
Keywords: التعليم الثانوي; التوافق الدراسي; التنمر المدرسي; School bullying; Academic adjustment; Secondary education